Application of intragenic DNA probes in prenatal screening for retinoblastoma gene carriers in the United Kingdom. Issue 7 (July 1990) - Onadim, Z O; Mitchell, C D; Rutland, P C; Buckle, B G; Jay, M; Hungerford, J L; Harper, K; Cowell, J K
Abstract : Restriction fragment length polymorphisms (RFLPs) in 55 families affected by retinoblastoma have been studied using recombinant DNA probes derived from within the retinoblastoma predisposition gene. Only six families were uninformative for any of the DNA polymorphisms. The remaining 49 families can be offered prenatal screening. No obligate recombinations between any of the polymorphic loci and the retinoblastoma phenotype were observed. Four previously unknown cases of non-penetrance were identified. Prenatal testing for the inheritance of mutant alleles was performed in two cases and perinatal screening in two additional cases. One fetus inherited the normal allele from the affected parent and is therefore not at risk of retinoblastoma; the second fetus inherited the mutant allele and will require frequent screening for early detection of retinoblastoma. Both perinatal tests showed the absence of the mutant allele.